2017
DOI: 10.1007/s10620-016-4399-4
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Management After Transjugular Intrahepatic Portosystemic Shunt Placement According to Clinical Manifestations

Abstract: We propose an algorithm for management after transjugular intrahepatic portosystemic shunt (TIPS) placement according to clinical manifestations. For patients with an initial good clinical response, surveillance Doppler ultrasound is recommended to detect stenosis or occlusion. A TIPS revision can be performed using basic or advanced techniques to treat stenosis or occlusion. In patients with an initial poor clinical response, a TIPS venogram with pressure measurements should be performed to assess shunt paten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…There are many studies showing the benefits of a TIPS in treating PH that is refractory to medical therapy, including in cases of refractory ascites and variceal hemorrhage, and TIPSs have also been shown to improve survival in many settings ( 27 , 28 ). Potential complications of TIPSs include further hepatic decompensation, worsening hepatic encephalopathy, cardiac failure, TIPS dysfunction, and, in rare cases, death, and thus, proper patient selection is required ( 28 , 29 ).…”
Section: Treatment Of Portal Hypertensionmentioning
confidence: 99%
“…There are many studies showing the benefits of a TIPS in treating PH that is refractory to medical therapy, including in cases of refractory ascites and variceal hemorrhage, and TIPSs have also been shown to improve survival in many settings ( 27 , 28 ). Potential complications of TIPSs include further hepatic decompensation, worsening hepatic encephalopathy, cardiac failure, TIPS dysfunction, and, in rare cases, death, and thus, proper patient selection is required ( 28 , 29 ).…”
Section: Treatment Of Portal Hypertensionmentioning
confidence: 99%
“…In-stent stenosis most commonly occurs at the hepatico-caval junction. Multiple studies have shown that angioplasty with the placement of covered stents gives better long term results compared to angioplasty alone[ 248 ]. Restenting is also useful in cases of stent shortening or portal venous stenosis.…”
Section: Update On the Technical Aspects Of Tipsmentioning
confidence: 99%
“…After TIPS implantation, laboratory testings (including blood test, liver and kidney function and coagulation function) and imaging examinations (such as ultrasound, CT or MRI) were reexamined at 1, 3, 6, 12 months in the rst year and once a year here after. Phone calls were made regularly to keep up with the prognosis and complications of the patients and they were kept in detailed records [21].…”
Section: Follow Upmentioning
confidence: 99%